2009
DOI: 10.1111/j.1365-2923.2009.03407.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive validity of the multiple mini-interview for selecting medical trainees

Abstract: Further evidence for the validity of the MMI approach to making admissions decisions has been provided. More generally, the reported findings cast further doubt on the extent to which performance can be captured with trait-based models of ability. Finally, although a complementary predictive relationship has consistently been observed between grade point average and MMI results, the extent to which cognitive and non-cognitive qualities are distinct appears to depend on the scope of practice within which the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
215
1
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 245 publications
(245 citation statements)
references
References 25 publications
(40 reference statements)
11
215
1
13
Order By: Relevance
“…41,50,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] Eleven studies showed a positive correlation between interview and subsequent performance. 8,51,52,[68][69][70][71][72][73][74][75] Performance metrics with a positive correlation included clinical evaluations, in-training examinations, licensing board examinations, and a composite score or rank of resident performance. Attrition from residency was not consistently predicted by the interview process in the 6 studies that assessed this variable.…”
Section: Performancementioning
confidence: 99%
“…41,50,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] Eleven studies showed a positive correlation between interview and subsequent performance. 8,51,52,[68][69][70][71][72][73][74][75] Performance metrics with a positive correlation included clinical evaluations, in-training examinations, licensing board examinations, and a composite score or rank of resident performance. Attrition from residency was not consistently predicted by the interview process in the 6 studies that assessed this variable.…”
Section: Performancementioning
confidence: 99%
“…Despite their importance, it remains unclear how best to measure these characteristics, particularly in the context of high-stakes testing where applicants may be motivated to distort their responses (Albanese et al, 2003;Bore et al, 2009;Musson, 2009;Patterson et al, 2016). In recent years, a variety of selection tools have been developed that aim to assess these noncognitive characteristics, including situational judgment tests (Bore et al, 2009;De Leng et al, 2017;Lievens, 2013;Patterson et al, 2012;Patterson et al, 2009), multiple mini-interviews (Eva et al, 2014;Eva et al, 2009;Eva et al, 2004;Griffin et al, 2012a;Kulasegaram et al, 2010), emotional intelligence tests (Libbrecht et al, 2014), and personality tests (Griffin et al, 2012b;MacKenzie et al, 2017;Rothstein et al, 2006). The current study focuses on personality testing in the context of the high-stakes selection of medical interns assessing the degree to which response distortion might limit the utility of personality tests.…”
Section: Introductionmentioning
confidence: 99%
“…Although research has shown that the MMI process is fair [15], previous studies have indicated that the reliability of MMIs may vary widely depending on the way they are administered and structured [2,5]. Moreover, research indicates that examiner subjectivity and station difficulty would have affected the fairness of the test in MMIs [11,16].…”
Section: Introductionmentioning
confidence: 99%